2017
DOI: 10.18632/oncotarget.14523
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta1 suppresses hepatocellular carcinoma proliferation via activation of Hippo signaling

Abstract: In this study, we examined the expression of core proteins of the Hippo signaling pathway in hepatocellular carcinoma (HCC) cells treated with transforming growth factor-β 1(TGF-β1) and investigated the relationship between TGF-β1 and the Hippo signaling pathway, in order to better understand their roles in HCC and their potential implications for cancer therapy. We prove that the Hippo signaling pathway is involved in the TGF-β1-induced inhibition of the growth of HCC cells. Large tumor suppressor expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Additionally, reduced TβRII staining has been observed in approximately 25% of malignant compared to adjacent nonmalignant hepatocytes [91]. TGF-β was also found to suppress HCC proliferation through activating Hippo signaling [92]. NADPH oxidase 4 may mediate the antiproliferative and proapoptotic effects of TGF-β in HCC cells [93].…”
Section: Role Of Tgf-β Signal In Gastrointestinal Cancersmentioning
confidence: 99%
“…Additionally, reduced TβRII staining has been observed in approximately 25% of malignant compared to adjacent nonmalignant hepatocytes [91]. TGF-β was also found to suppress HCC proliferation through activating Hippo signaling [92]. NADPH oxidase 4 may mediate the antiproliferative and proapoptotic effects of TGF-β in HCC cells [93].…”
Section: Role Of Tgf-β Signal In Gastrointestinal Cancersmentioning
confidence: 99%
“…Zhang et al found that TGF-β-induced expression of large tumor suppressor 1 (LATS1) and nucleus-cytoplasm translocation of yes association protein 1 (YAP1) resulted in cell growth inhibition in HCC cells. 45 Chen et al screened almost 1,000 HCCs, clustering patients into subsets with mutational loss or gain of TGF-β pathway activation. Interestingly, patients with the inactivated TGF-β pathway (showing reduced TGFB1, SMAD3, and SMAD4) exhibited a loss of the tumor suppressor genes required for DNA damage repair (ATM, BRCA1, and FANCF), an aberrant expression of pro-oncogenic genes, such as sirtuin and HDAC, and had shorter survival times than those with the activated TGF-β pathway status.…”
Section: Tgf-β In the Pathogenesis Of Hccmentioning
confidence: 99%
“…demonstrated that TGFβ upregulates the expression of the CD44 cancer-related CD44V6 isoform through EGR1-mediated AP-1 (activator protein-1) activation in pulmonary fibroblasts. Nevertheless, other studies have clearly highlighted the capacity of TGFβ to restrain the pro-tumorigenic potential of HCC cells, via inducing the expression of tumor suppressors genes, such as LATS1, or DNA damage repair proteins (ATM, BRCA1, and FANCF) 56,57 . A further layer of complexity of the TGFβ role in HCC is suggested by the positive correlation between TGFβ and poor survival, observed only in the patients' subset expressing low PRG4 levels (see Fig.…”
Section: Discussionmentioning
confidence: 99%